First report of Garella musculana (Erschov, 1874) (Lepidoptera: Nolidae) in Italy with insights into its identity. (13th December 2022) - Scaccini, Davide; Bramuzzo, Davide; Bostancı, Cengiz; Faccoli, Massimo; Martinez‐Sañudo, Isabel; Matov, Alexey; Zilli, Alberto; Pozzebon, Alberto
Abstract: The Asian walnut moth, Garella musculana (Erschov, 1874) (Lepidoptera: Nolidae), is a major pest of walnut. Native to Central Asia, it was found to be invasive in 2008 in Sevastopol (Crimea) and nowadays widespread in Turkey, Bulgaria, Romania and Russia. Here, we account for the finding of G. musculana in NE Italy (Veneto region) in 2021, where adults were found in a light lamp, representing the first record of the Asian walnut moth for this country and Western Europe. Adult specimens were identified morphologically on both external characters and genitalia features. G. musculana larvae and damage were also observed on a plantation of Juglans regia L. (Fagales: Juglandaceae) located in Veneto in October 2021. A COI‐barcoding analysis was performed to attain a molecular characterization of our specimens and probate our morphological identification. However, because no sequence of G. musculana was present in major gene databases and the similarity of our sequences with those attributed to Garella ruficirra (Hampson, 1905) (Lepidoptera: Nolidae) made clear that these taxa deserved further scrutiny regarding their specific distinction. Some subtle differences in the male terminalia could be found between them and their vast geographic distributions, but the strong similarity in most features calls for further morphological and genetical insights on a broad set of samples to assess whether they represent two closely related, substantially parapatric species, or a unique, geographically varying entity. Solving this issue may turn out crucial in the identification and proper management of walnut moths of the genus Garella .